Software-defined radio readout system for the ECHo experiment - Sander, Oliver; Karcher, Nick; Krömer, O.; Kempf, Sebastian; Wegner, Mathias; Enss, Christian; Weber, Marc (IEEE transactions on nuclear science, 2019)
Metallic magnetic calorimeters (MMCs) are highly linear cryogenic detectors that offer an excellent energy resolution, a signal rise time of <;100 ns, and a high dynamic range. MMCs are of high interest for many experiments. One of them, i.e., the Electron Capture (EC) in 163Ho (ECHo) experiment, requires the utilization of large MMC detector arrays. The readout of such MMC arrays is a challenging task, which can be tackled using software-defined radios (SDRs). Although SDR is a well-known approach in communications engineering, a dedicated implementation for frequency division multiplexed readout of MMCs is new and one of the technological key elements of the ECHo project. ECHo will be the first experiment to use microwave superconducting quantum interference device (SQUID) multiplexed MMC detectors, and therefore, pioneering the hardware, firmware, and software development in this domain. This paper presents the detailed concepts and current status of the development.